PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN MANUFAKTUR (Studi Empiris Pada Perusahaan Farmasi yang Tercatat Di BEI Tahun 2013-2017) - Novi Anggita; M Agus Salim; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThis study aims to determine and analyze the effect of profitability, company size, debt policy partially on the value of manufacturing companies. The technique used in sampling is purposive sampling technique, the technique of determining sample is consideration of certain criteria. The analysis technique used is descriptive quantitative using multiple linear regression analysis and also through t test using the SPSS program.Based on the results of the data analysis partially shows that profitability has a positive and not significant effect on firm value, firm size has no significant positive effect on firm value and debt policy has no significant positive effect on firm value. Based on the research results obtained to the company it is suggested that it can improve the performance of fiber companies financial performance so that the prospects of investors towards the company will be better. To investors, the authors suggest that they be more careful and selective in making decisions to invest. Keywords: Profitability, Company Size and Debt Policy and the Value of the Company.